Polycaprolactone fiber meshes provide a 3D environment suitable for cultivation and differentiation of melanocytes from the outer root sheath of hair follicle. Issue 1 (16th July 2015) - Savkovic, Vuk; Flämig, Franziska; Schneider, Marie; Sülflow, Katharina; Loth, Tina; Lohrenz, Andrea; Hacker, Michael Christian; Schulz‐Siegmund, Michaela; Simon, Jan‐Christoph
Abstract: Melanocytes differentiated from the stem cells of human hair follicle outer root sheath (ORS) have the potential for developing non‐invasive treatments for skin disorders out of a minimal sample: of hair root. With a robust procedure for melanocyte cultivation from the ORS of human hair follicle at hand, this study focused on the identification of a suitable biocompatible, biodegradable carrier as the next step toward their clinical implementation. Polycaprolactone (PCL) is a known biocompatible material used for a number of medical devices. In this study, we have populated electrospun PCL fiber meshes with normal human epidermal melanocytes (NHEM) as well as with hair‐follicle‐derived human melanocytes from the outer root sheath (HUMORS) and tested their functionality in vitro . PCL fiber meshes evidently provided a niche for melanocytes and supported their melanotic properties. The cells were tested for gene expression of PAX3, PMEL, TYR and MITF, as well as for proliferation, expression of melanocyte marker proteins tyrosinase and glycoprotein 100 (gp100), L‐DOPA‐tautomerase enzymatic activity and melanin content. Reduced mitochondrial activity and PAX‐3 gene expression indicated that the three‐dimensional PCL scaffold supported differentiation rather than proliferation of melanocytes. The monitored melanotic features of both the NHEM and HUMORS cultivated on PCL scaffolds significantly exceeded those of two‐dimensional adherent cultures. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 26–36, 2016.